Personality Type D, Level of Perceived Stress, Insomnia, and Depression Among High School Teachers in Poland - Domagalska, Joanna; Rusin, Monika; Razzaghi, Mehdi; Nowak, Przemysław (Frontiers in Psychology, 2021)
Teaching is inherently connected with specific burdens that may imply stressful situations. The goal of this study was to explore the prevalence of type D (distressed) personality in teachers. This is known to cause depressive episodes and sleep disorders, which not only have direct physical health effects, but can also impact the wellbeing of individuals and hence adversely affect their job performance. The participants consisted of 412 high school teachers from the Silesian Province, located in the south of Poland. Using the following research tools: Type D Scale (DS14), Perceived Stress Scale, Athens Insomnia Scale, and Beck Depression Inventory, it was found that type D personality was observed in a large percentage of teachers (30.1%). It was reported that teachers with distressed personality suffered from insomnia and depression significantly more often. Findings from the current study indicate the need to implement preventive activities focused on reducing psychosocial risk factors in the work environment in order to reduce the frequency of depressive disorders among teachers.